Lakumasaurus antarcticus, n. gen. et sp., a new mosasaur (Reptilia, Squamata) from the Upper Cretaceous of Antarctica - Novas, Fernando Emilio; Fernández, Marta Susana; de Gasparini, Zulma B.; Lirio, Juan Manuel; Nuñez, Héctor J.; Puerta, Pablo
Mosasaurs were large predatory lizards that typically inhabited warm, epicontinental seas during the last 20 million years of the Mesozoic Era. Evidence of their taxonomic diversity derives mainly from significant finds from Late Cretaceous rocks of North America, Europe, and northern Africa (e.g., Russell, 1967; Lingham-Soliar, 1991, 1992; Bell, 1997). In contrast, the mosasaur record from the Southern Hemisphere is partial and much less informative (e.g., Welles and Gregg, 1971; Wiffen, 1980, 1990; Páramo, 1994; Bell et al., 1998; Caldwell and Bell, 1995; Gasparini et al., 2001). Mosasaur remains from Antarctica are mostly limited to isolated teeth and fragmentary bones (Gasparini and Del Valle, 1981, 1984; Chatterjee and Zinsmeister, 1982), thus restricting their potential implications for mosasaur phylogeny and paleobiogeography. Here we report on a new tylosaurine mosasaur, Lakumasaurus antarcticus gen. et sp. nov., discovered in the Late Cretaceous beds of James Ross Island, northeast Antarctic Peninsula. Lakumasaurus is the most complete mosasaur yet recorded in Antarctica, thus providing insights on mosasaur diversification in the southern seas. This discovery, together with Late Cretaceous mosasaur remains from New Zealand, suggests that distinctions between Cretaceous marine reptile faunas of the Southern and Northern hemispheres were greater than has been thought. Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Fernández, Marta Susana. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: de Gasparini, Zulma B. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina ...